2022
DOI: 10.3390/bs12110457
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Importance of Gender, Family Affluence, Parenting Style and Loneliness in Cyberbullying Victimization and Aggression among Romanian Adolescents

Abstract: The increasing phenomenon of cyberbullying among adolescents needs parental, educational, and social intervention. The study aimed to identify the prevalence of cyberbullying among Romanian adolescents and the importance of gender, family-related factors, self-esteem, and parental styles in both victims and perpetrators. A total of 835 adolescents aged 10–19 years were included in the research. An online questionnaire was specially constructed for this research, gathering socio-demographic and family-related d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
0
9
0
1
Order By: Relevance
“…This result is inconsistent with the study of cyberbullying victimization among Romanian adolescents. The researchers found that girls have low level of selfesteem because they are exposed to cyberbullying more than boys [21].…”
Section: Discussionmentioning
confidence: 99%
“…This result is inconsistent with the study of cyberbullying victimization among Romanian adolescents. The researchers found that girls have low level of selfesteem because they are exposed to cyberbullying more than boys [21].…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, parents influence children's susceptibility to cyberbullying through their parenting practice and oversight. For instance, a study involving Romanian adolescents demonstrated that a supportive parenting style serves as a protective factor, shielding adolescents from cyberbullying victimization ( 21 ). Similarly, Wu et al found that parental rejection from both fathers and mothers increases children's risk of experiencing cyberbullying, slowing down the decline in such victimization over time ( 22 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, the quality of parent-child relationship is a key predictor of children's vulnerability to cyberbullying. Adolescents who have a more positive and satisfying relationship with their parents are less likely to experience cyberbullying ( 21 , 24 ). Liu and Chen found that parent-child closeness plays a crucial role in reducing the risk of adolescents being victims in cyberbullying ( 25 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Установлено, что благополучие семьи, общение с родителями и одноклассниками, наличие одиночества и социально-демографические факторы тесно связаны с наличием агрессии и/или жертвенности среди подростков. Результаты имеют решающее значение для выявления участников кибербуллинга и предотвращения негативного влияния кибербуллинга на психологическую, социальную и академическую жизнь учащихся, родителей и учителей [9].…”
Section: таблица 1 виды кибербуллингаunclassified